2013
DOI: 10.12688/f1000research.2-25.v1
|View full text |Cite
|
Sign up to set email alerts
|

Association of spirochetal infection with Morgellons disease

Abstract: Morgellons disease (MD) is an emerging multisystem illness characterized by skin lesions with unusual filaments embedded in or projecting from epithelial tissue. Filament formation results from abnormal keratin and collagen expression by epithelial-based keratinocytes and fibroblasts. Recent research comparing MD to bovine digital dermatitis, an animal infectious disease with similar skin features, provided clues that spirochetal infection could play an important role in the human disease as it does in the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…Middelveen et al34 reported that this disorder was associated with spirochetal infection ( B. burgdorferi ). Culture, histology, immunohistochemistry, electron microscopy, and molecular testing verified that Morgellons disease could be associated with a systemic spirochetal infection3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Middelveen et al34 reported that this disorder was associated with spirochetal infection ( B. burgdorferi ). Culture, histology, immunohistochemistry, electron microscopy, and molecular testing verified that Morgellons disease could be associated with a systemic spirochetal infection3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized as a delusional infestation2. However, recent studies are suggesting that it could be associated with an infectious organism: Borrelia burgdorferi 34. There have been a number of reports and investigations about Morgellons disease in the US or Europe, but there are none so far in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Both Bb and RFB have been consistently detected in MD specimens. 12,13,15,17,18 Although other pathogens have been detected in MD dermatological specimens, Borrelia spirochetes are the pathogens most consistently detected in MD lesions. Therefore, our proposed staging system focuses on the infectious patterns of Borrelia spp.…”
Section: Infection Associated With MDmentioning
confidence: 99%
“…However, patients with MD have a visible manifestation of infection that is easily identifiable by the MD case definition, and spirochetal infection is detectable in dermatological tissue by direct detection methods, providing that the correct methodologies are used. 8,9,12,13,15,17,18 Methodologies that should be accepted as corroborative diagnostic evidence of spirochetal infection in MD patients should include those that can directly detect Borrelia spirochetes in skin specimens from tissue showing dermopathy. This can be accomplished by histological sectioning and staining with silver stains, IHC, FFM and or FISH; and by DNA detection using PCR technology.…”
Section: Diagnostic Approach To Ld and MDmentioning
confidence: 99%
See 1 more Smart Citation